The world is waiting, use sequential analysis and get us the evidence-based treatment we need for COVID-19. Issue 1 (1st January 2020) - El Taguri, Adel; NASEF, Aisha
ABSTRACT: In spite of the relatively high morbidity and mortality, there is no approved medication yet for COVID-19. There are more than 200 ongoing trials on different drugs or vaccines, but new medications may take until 2021 to develop. Defining the optimal number of patients to be included in a study is a considerable challenge in these interventional researches. Ethical considerations prompt researchers to minimize the number of patients included in a trial. This gains particular importance when the disease is rare or lethal which is particularly so in the case of COVID-19. It is of paramount importance to explore some of the available tools that could help accelerate the adoption of any or some of the many proposed modalities for the treatment of diseases. These tools should be effective, yet efficient, for rapid testing of such treatments. Sequential analysis has not been frequently used in many clinical trials where it should have been used. None of the authors in published literature, as far as we know, used sequential analysis techniques to test potential drugs for COVID-19. In addition to its usefulness when the results of new forms of treatment are quickly needed, other important benefit of sequential analysis includes the ability to reach a similar conclusion about the utility of a new drug without unduly exposing more patients to the side effect of the old drug, in particularly, for the treatment of a rare disease.